The Effectiveness of Counseling on Husband's Support in Early Detection of Cervical Cancer Acetic Acid Visual Inspection Method IVA - Aprilia Aristyawati; Shanty Natalia; Endah Pujiati; Siti Kholisah (Universitas STRADA Indonesia, 2023)
Low support from husbands to mothers for early detection of cervical cancer using the Acetic Acid Visual Inspection (IVA) method makes mothers not motivated to carry out early detection of cervical cancer. The purpose of this study was to analyze the effectiveness of counseling methods on husband's supportin carrying out early detection of cervical cancer with the IVA method at PMB Ardiniwati Tarik Sidoarjo.The research design is research quasi experimental with approach one group pretest-posttest design. Population and samples are all husbands of couples of childbearing age as many as 30 respondents. The sampling technique is total sampling, using the Wilcoxon test. Prior to counseling, the majority of respondents rarely provided support to their wives, as many as 21 (70%) of respondents. Most of the respondents often provide support to their wives as many as 17 (57%) of respondents. Based on the results of the Wilcoxon test, the p-value is 0.000, which means that the p-value is less than α 0.05, meaning that there is a difference between husband's support and in carrying out early detection of cervical cancer with the IVA method before and after counseling. The importance of husband's support for his wife so that the wife is motivated to carry out early detection of cervical cancer using the IVA method.